Quality of Socialization, Services, and Electronic Services on Taxpayer Satisfaction and Taxpayer Compliance at Kantor Pelayanan Pajak Madya Pekanbaru - Pratomo Aji Saputro; Mimelientesa Irman; Harry Patuan Panjaitan (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of this study is to analyze and determine the effect of socialization quality, service quality, and electronic service quality on taxpayer satisfaction and taxpayer compliance. The population in question is taxpayers who are registered with the KPP Madya Pekanbaru and have the obligation to report the Annual Income Tax Return using e-filing, totaling 829 taxpayers. The sample was used using the Slovin formula calculation of as many as 109 respondents. The data analysis technique in this study used descriptive analysis and Structural Equation Model – Partial Least Square (SEM-PLS) analysis with the help of Smart PLS software. The results of this study indicate that the quality of service and the quality of electronic services is significantly positive for taxpayer satisfaction and socialization quality is positively not significant for taxpayer satisfaction. Quality of socialization, quality of service, quality of electronic services, and taxpayer satisfaction are positive but not significant on taxpayer compliance.